National Education Plan and the issue of innovation in pedagogical practices (Research, Society and Development, 2022)
This article aims to discuss the importance of Brazilian public policies in the current context of the Basic School, as well as the relevance of the current National Education Plan, questioning the innovation of pedagogical practices in the Basic School. We sought to understand what the 2014/2024 National Education Plan can bring to Basic Education on Innovation. The approach used in this article was a qualitative approach, with a bibliographic character, the materials used were found in the SciELO portal (Scientific Electronic Library Online), CAPES Periodicals Portal (Coordination for the Improvement of Higher Education Personnel) and the PNE law found on the Senate (Federal Government) portal. As a result of the discussion, the importance of pedagogical innovation for Basic Education is remarkable, forming citizens who can understand the world, according to the reality in which they live. It was concluded that the current PNE brings little contribution to improving quality, in the goals the word innovation appears few times, without unfolding how it should be in the pedagogical practice of Brazilian schools. It is understood that the PNE should discuss and induce the possibility of pedagogical innovation aiming at advances in the educational area.